Breast Self-Examination: Knowledge, Practice, and Beliefs Among Females in Jordan - Suhad Ahmad MSc; Aladeen Alloubani PhD; Ruba Abu-Sa'da MSc; Yasar Qutaiba MD (SAGE Publishing, 2022)
Introduction Worldwide, breast cancer is one of the most common types of cancer. It is the leading cause of cancer-related deaths among females in Jordan. Objective(s) The current study aimed to evaluate breast cancer knowledge levels and practice and assess health beliefs regarding the model supporting self-breast examination (BSE) in a group of females aged between 20 and 60 in Jordan. Methods Descriptive, cross-sectional, correlational design was used; Two hundred females participated in the study, employing convenient sampling. The adjusted version of the Champion's Health Belief Model Scale (CHBMS) was utilized to collect the data. Results Most participants were married (F = 128, 64%), and the mean of the participants' age was (36.18, SD  = 10.87). About 73 participants (36.5%) don't practice BSE; however, 53 participants (26.5%) plan to practice BSE in the future monthly. The logistic regression model showed that the impact of confidence as positive predictive value on practicing BSE in the last year ( B  = 0.141, p < .001) and this year ( B  = 0.130, p < .001) was statistically significant. Conclusion Implications for practice include identifying culturally specific barriers and improving health education programs to trigger breast self-examination utilization.